2018
DOI: 10.1016/j.ijheh.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated alkyl acids in the serum and follicular fluid of UK women with and without polycystic ovarian syndrome undergoing fertility treatment and associations with hormonal and metabolic parameters

Abstract: Women with polycystic ovarian syndrome (PCOS) undergoing treatment for infertility could be a sensitive subpopulation for endocrine effects of exposure to perfluorinated alkyl acids (PFAAs), persistent organic pollutants with potential endocrine activity. Women with, PCOS (n = 30) and age- and BMI-matched controls (n = 29) were recruited from a UK fertility clinic in 2015. Paired serum and follicular fluid samples were collected and analysed for 13 PFAAs. Sex steroid and thyroid hormones, and metabolic markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 63 publications
3
48
0
2
Order By: Relevance
“…Heffernan et al . found a positive association between PFNA exposure and A4 in both PCOS cases and controls, and a positive association between PFHxS exposure and total T in healthy women ( Heffernan et al , 2018 ). Zhang et al .…”
Section: Epidemiologic Evidence Linking Pfas Exposure and Ovarian Outmentioning
confidence: 95%
See 3 more Smart Citations
“…Heffernan et al . found a positive association between PFNA exposure and A4 in both PCOS cases and controls, and a positive association between PFHxS exposure and total T in healthy women ( Heffernan et al , 2018 ). Zhang et al .…”
Section: Epidemiologic Evidence Linking Pfas Exposure and Ovarian Outmentioning
confidence: 95%
“…Due to the ability of albumin to pass the blood follicle barrier ( Hess et al , 1998 ; Schweigert et al , 2006 ), it is suggested that PFAAs can easily be transported into growing follicles. PFAAs have been detected in human follicular fluid and could alter oocyte maturation and follicle development in vivo ( Petro et al , 2014 ; Heffernan et al , 2018 ).…”
Section: Basic Principles Of Pfasmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently there are no reports concerning the experimental evaluation of the dominant perfluoroalkyl acid detected in the environment, PFOA, on oocyte toxicity in mammals. However, levels of PFC, including PFOA, have been detected in the follicular fluid of women, and it was reported that women with follicular fluid PFC contamination had significantly lower fertilization rate and number of embryos transferred compared to the PFC negative group in patients undergoing IVF‐ET cycles, thus indicating possible deleterious effects of PFOA and other PFC on mammal's oocytes . Therefore, the objective in the present study was to investigate whether PFOA was able to generate ROS in murine fetal ovaries (early oogenesis) and cause oocyte death by apoptosis and/or necrosis in fetal oocytes in culture.…”
Section: Introductionmentioning
confidence: 99%